Health Insurance Policy and Customer Behavior - Ahir, Bhakti Ishwar; Vitthal, Pimple Vandana (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
A health insurance policy can protect yourself and your family from healthcare expenses and play a vital role in reducing the financial burden. According to a well-known report, heart disease kills at least two people every minute, while about 5,000 children die from various diseases. Cancer kills hundreds of people every day, and India ranks third in deaths due to malaria. At least 500 road accidents occur in India every day, out of which about 200 people die due to lack of healthcare facilities and lack of timely treatment. In all such situations, we can understand how much each person needs health insurance. However, if we want to understand more, we should go to the hospital and realize how safe we are. Be it rich or poor, male or female, young or old, getting diagnosed with an accident and getting treatment in the hospital has become a big problem for everyone. Therefore, having health insurance has become the need of the hour. The incidence of many diseases like heart disease, diabetes, stroke, kidney failure, cancer is increasing. For some time now, special attention has been paid to each of these diseases. The availability of hospitals and specialist doctors has increased but all these are very expensive. The very rich people can afford them but the middle class or poor people cannot afford the cost of admission to the hospital and the cost of treatment there. Therefore, a health insurance policy can cover such expenses. Therefore, the need for health insurance services and the need of the people for it is increasing rapidly. Therefore, it was considered more important to write a research article on this topic.